Effect of drying temperature on microstructural, mechanical, and water barrier properties of konjac glucomannan/agar film produced at industrial scale. (1st January 2023) - Qin, Jiaming; Xiao, Man; Wang, Shuangshuang; Peng, Chun; Wu, Xiaohe; Jiang, Fatang
Abstract: Konjac glucomannan (KGM)/agar blend films were obtained by casting at different drying temperatures (40 °C, 50 °C, 60 °C, 70 °C, and 80 °C) at an industrial scale. The effects of the drying temperature on the microstructure, mechanical, and water barrier properties of the films were investigated. The results showed that lower temperatures (40 °C, 50 °C, and 60 °C) led to enhanced H-bond interactions between KGM and agar and more ordered structures of KGM/agar films, as evidenced by FTIR and X-ray analysis. Correspondingly, the mechanical properties were altered with the film's structure and showed significant differences ( p < 0.05) at various drying temperatures. Moreover, the drying temperatures from 40 °C to 80 °C had no significant influence ( p > 0.05) on the water vapour permeability of the films. The film dried at 60 °C showed significantly higher water contact angle and lower swelling ratio and solubility than the other films. Additionally, the drying temperature of 60 °C gave the highest thermal degradation temperature. Therefore, 60 °C was recommended for KGM/agar film production. This research guides the selection of the optimal drying temperature for edible film production. Highlights: KGM/agar films were produced by casting at different drying temperatures. The microstructure of the films was greatly affected by the drying temperature. The mechanical properties of the films were dependent upon the drying temperature. The recommended drying temperature on KGM/agar film should be 60 °C.